Bibliometric Analysis of Publications Related to the Implementation of Agile Methodologies In Project Management in IT Companies, in the Period 2010-2021 - Bendezu Herencia, Paola Katherine (2023)
Software development in IT companies is a whole process, so it is important to define the ideal methodology before starting a project. This study describes the literature on project management in 2 periods 2010-2019 and 2020-2021, through a bibliometric review of research indexed in Scopus and Web of Science. The VosViewer tool has been used to visualize the relationships between authors and keywords. A total of 666 publications related to agile methodologies were identified during 2010-2021. The institutions with the highest publishing activity were concentrated in the US, Brazil and Germany. The co-authorship and co-occurrence analyze of keywords show the main authors and research sources in both periods. Publications on agile methodologies in IT companies have been increasing in the last 2 years. In this research, the main authors, journals, thematic areas, institutions, countries and cases of greater scientific relevance were analyzed.